Assessing the structural behaviour of square hollow glass columns subjected to combined compressive and impact loads via full-scale experiments. (15th July 2017) - Kalamar, Roman; Bedon, Chiara; Eliášová, Martina
Highlights: Full-scale experimental assessment of the performance of glass columns under impact. Various impact configurations are investigated, including soft or hard bodies. Preliminary damaged column is also analysed, to assess the effects of imperfections. The global performance of the examined full-scale columns is critically discussed. Local effects, crack propagation and collapse mechanisms are further explored. Abstract: Glass is largely used in buildings as a novel construction material. Due to the intrinsic mechanical properties of such material, however, specific design recommendations are demanded in order to offer appropriate "fail-safe" requirements. This is especially true in the case of load-bearing structural glass elements where redundancy, stability and residual resistance should be guaranteed. In this regard, based also on a past research effort, the paper experimentally investigates the structural performance of full-scale square hollow glass columns, whose resisting cross-section consists of four adhesively joined laminated glass panes. Impact tests are carried out on in-plane compressed specimens, including both a reference undamaged column and a deliberately, preliminary broken specimen. The effects of multiple impact test configurations (inclusive of various release configurations for the impact mass as well as type of impact body) are hence emphasized, with critical discussion of the observed overall results and failure mechanisms.